Normalization of Enzyme Expression and Activity Regulating Vitamin A Metabolism Increases RAR-Beta Expression and Reduces Cellular Migration and Proliferation in Diseases Caused by Tuberous Sclerosis Gene Mutations - Abdelwahab, Elhusseiny Mohamed Mahmoud; Bovari-Biri, Judit; Smuk, Gabor; Harko, Tunde; Fillinger, Janos; Moldvay, Judit; Krymskaya, Vera P.; Pongracz, Judit E. (Frontiers in Oncology, 2021)
Background Mutation in a tuberous sclerosis gene (TSC1 or 2) leads to continuous activation of the mammalian target of rapamycin (mTOR). mTOR activation alters cellular including vitamin A metabolism and retinoic acid receptor beta (RARβ) expression. The goal of the present study was to investigate the molecular connection between vitamin A metabolism and TSC mutation. We also aimed to investigate the effect of the FDA approved drug rapamycin and the vitamin A metabolite retinoic acid (RA) in cell lines with TSC mutation. Methods Expression and activity of vitamin A associated metabolic enzymes and RARβ were assessed in human kidney angiomyolipoma derived cell lines, primary lymphangioleiomyomatosis (LAM) tissue derived LAM cell lines as well as RARβ protein levels were tested in primary LAM lung tissue sections. TaqMan arrays, enzyme activities, qRT-PCRs, immunohistochemistry, immunofluorescent staining and western blotting were performed and analysed. The functional effects of retinoic acid (RA) and rapamycin were tested in a scratch and a BrDU assay to assess cell migration and proliferation. Results Metabolic enzyme arrays revealed a general deregulation of many enzymes involved in vitamin A metabolism including aldehyde dehydrogenases (ALDHs), alcohol dehydrogenases (ADHs) and Cytochrome P450 2E1 (CYP2E1). Furthermore, RARβ downregulation was a characteristic feature of all TSC-deficient cell lines and primary tissues. Combination of the two FDA approved drugs -RA for acute myeloid leukaemia and rapamycin for TSC mutation- normalised ALDH and ADH expression and activity, restored RARβ expression and reduced cellular proliferation and migration. Conclusion Deregulation of vitamin A metabolizing enzymes is a feature of TSC mutation. RA can normalize RARβ levels and limit cell migration but does not have a significant effect on proliferation. Based on our data, translational studies could confirm whether combination of RA with reduced dosage of rapamycin would have more beneficial effects to higher dosage of rapamycin monotherapy meanwhile reducing adverse effects of rapamycin for patients with TSC mutation.